Ascorbigen A-NMR identification - Sychrovský, Vladimír; Šaman, David; Fiala, Radovan; Humpa, Otakar; Sýkora, Jan; Kessler, Pavel; Blechta, Vratislav; Dobrev, Petre; Schraml, Jan (Magnetic resonance in chemistry, 2019)
The connectivities of all atoms in ascorbigen A, an important metabolite, were determined unambiguously for the first time. The connectivity between carbon atoms was established by 2D INADEQUATE, and one-bond 13 C-13 C coupling constants were determined for all pairs of directly connected carbon atoms except for two strongly coupled carbon pairs. The 13 C-13 C coupling in one of the pairs was proved by a modification of standard INADEQUATE; however, the signals from the other pair were too weak to be observed. The connectivity within the two strongly coupled C-C pairs was confirmed by a combination of COSY and gHSQC; the latter experiment also identified all C-H bonds. The proton nuclear magnetic resonance (1 H NMR) spectra in dry dimethyl sulfoxide allowed identification and assignment of the signals due to NH and OH protons. The derived structure, 3-((1H-indol-3-yl)methyl)-3,3a,6-trihydroxytetrahydrofuro[3,2-b]furan-2(5H)-one, agrees with the structure suggested for ascorbigen A in 1966. The density functional theory (DFT) calculations showed that among 16 possible stereoisomers, only two complied with the almost zero value of the measured 3 J(H6-H6a). Of the two stereoisomers, 3S,3aS,6S,6aR and 3R,3aR,6R,6aS, the latter was excluded on synthetic grounds. The nuclear Overhauser effect measurements unveiled close proximity between H2' proton of the indole and the H6a proton of the tetrahydrofuro[3,2-b]furan part. Detailed structural interpretation of the measured NMR parameters by means of DFT NMR was hampered by rotational flexibility of the indole and tetrahydrofuro[3,2-b]furan parts and inadequacy of Polarizable Continuum Model (PCM) solvent model.
Keywords: Ascorbic Acid; teorie funkcionálu hustoty; Indoles; molekulární konformace; indoly; 1H-1H coupling constants; 13C NMR; 13C-1H coupling constants; rotamers; NMR; Molecular Conformation; magnetická rezonanční spektroskopie; Density Functional Theory; NOE; natural product; kyselina askorbová; 13C-13C coupling constants; stereochemistry; 1H NMR; Magnetic Resonance Spectroscopy